Toward a feminist agroecology - Zaremba, Haley; Elias, Marlène; Rietveld, Anne M.; Bergamini, Nadia (MDPI, 2021)
Agroecology is gaining ground as a movement, science, and set of practices designed to advance a food systems transformation which subverts the patterns of farmer exploitation currently entrenched in dominant agricultural models. In order for agroecology to achieve its espoused twin aims of social and ecological wellbeing, women and other historically marginalized stakeholders must be empowered and centered as the movement’s protagonists. The importance of gender and social considerations is not limited to patently social aspects of the agroecological agenda, but bears relevance in every dimension of agroecology. Yet, issues related to gender have commanded relatively little attention in the agroeocological literature. In this paper, we review HLPE’s 13 defining principles of agroecology through a feminist lens to demonstrate the ways in which human dimensions and power dynamics are interwoven in every principle. Through this analysis, we demonstrate that a feminist approach is instrumental to establish a socially just and ecologically sustainable agroecological transition.